Making German history in Los Angeles: German Jewish refugees and West German diplomats in the 1950s and 1960s. Issue 1 (3rd May 2016) - Schenderlein, Anne C.
Abstract: In the 1930s and 1940s, several 1000 Jewish refugees from Nazi Germany arrived in Los Angeles. Most of them were eager to Americanize and did not intend to return to Germany, but nevertheless they retained an interest in their home country, and this increased after the end of the Second World War. Focusing on interactions between German Jewish refugees in Los Angeles and West German officials, this article explores relations between refugees and the Federal Republic of Germany and argues that, in acting as critical observers and moral arbiters of German policy from within the United States, the refugees played a role in the making of West Germany.